Implementasi Simulasi Realitas Virtual dalam Pendidikan Keperawatan Jiwa: Tinjauan Pustaka - Diorarta, Raphita; Sukihananto, Sukihananto (Universitas Pelita Harapan, 2025)
One of the medical diagnoses of mental disorders that is part of education in psychiatric nursing is schizophrenia. Part of the education of psychiatric nursing provides important information about mental disorders and learns new skills to deal with various challenging behaviors. The anxiety felt by psychiatric nursing students are normal and usually do not continue after students have initial contact with patients. Aim on this study is to explore the effectiveness of VR-based simulations in enhancing the skills of nursing students in caring for patients with mental health disorders. This study method uses literature review. The literature used in this study consists of journals sourced from Wiley Online, ScienceDirect, and Google Scholar between 2015 and 2024. Article selection used the protocol guidelines (PRISMA) of identification, screening, eligibility and resulted in 10 articles being analyzed. VR simulations provide immersive and realistic environments where students can safely practice therapeutic communication, conduct mental health assessments, and develop critical thinking skills. Research indicates that VR simulations significantly enhance students' skills, knowledge, and empathy in psychiatric nursing. Despite their advantages, VR technologies face limitations, such as VR technology presents challenges such as technical difficulties. However, evidence suggests that VR-based training is a promising tool for advancing psychiatric nursing education by fostering essential skills and promoting behavioral health equity among future nurses.